The widespread impact of poor infection prevention and control policies and bad prescribing practices on hospital-acquired infections : who is liable? - Carstens, Pieter Albert, 1960- (University of Pretoria, 2019)
Mini Dissertation (MPhil)--University of Pretoria, 2018.